The Role of Satellite Telemetry Data in 21st Century Conservation of Polar Bears (Ursus maritimus) - Kristin L. Laidre; George M. Durner; Nicholas J. Lunn; Eric V. Regehr; Todd C. Atwood; Karyn D. Rode; Jon Aars; Heli Routti; Øystein Wiig; Markus Dyck; Evan S. Richardson; Stephen Atkinson; et al. (Frontiers in Marine Science, 2022)
Satellite telemetry (ST) has played a critical role in the management and conservation of polar bears ( Ursus maritimus ) over the last 50 years. ST data provide biological information relevant to subpopulation delineation, movements, habitat use, maternal denning, health, human-bear interactions, and accurate estimates of vital rates and abundance. Given that polar bears are distributed at low densities over vast and remote habitats, much of the information provided by ST data cannot be collected by other means. Obtaining ST data for polar bears requires chemical immobilization and application of a tracking device. Although immobilization has not been found to have negative effects beyond a several-day reduction in activity, over the last few decades opposition to immobilization and deployment of satellite-linked radio collars has resulted in a lack of current ST data in many of the 19 recognized polar bear subpopulations. Here, we review the uses of ST data for polar bears and evaluate its role in addressing 21 st century conservation and management challenges, which include estimation of sustainable harvest rates, understanding the impacts of climate warming, delineating critical habitat, and assessing potential anthropogenic impacts from tourism, resource development and extraction. We found that in subpopulations where ST data have been consistently collected, information was available to estimate vital rates and subpopulation density, document the effects of sea-ice loss, and inform management related to subsistence harvest and regulatory requirements. In contrast, a lack of ST data in some subpopulations resulted in increased bias and uncertainty in ecological and demographic parameters, which has a range of negative consequences. As sea-ice loss due to climate warming continues, there is a greater need to monitor polar bear distribution, habitat use, abundance, and subpopulation connectivity. We conclude that continued collection of ST data will be critically important for polar bear management and conservation in the 21 st century and that the benefits of immobilizing small numbers of individual polar bears in order to deploy ST devices significantly outweigh the risks.

Ensuring tests of conservation interventions build on existing literature - William J. Sutherland; Sergio Ticul Alvarez‐Castañeda; Tatsuya Amano; Roberto Ambrosini; Philip Atkinson; John M. Baxter; Alexander L. Bond; Philip J. Boon; Katherine L. Buchanan; Jos Barlow; Giuseppe Bogliani; Olivia M. Bragg; et al. (Conservation Biology, 2020)

Recent shoreline evolution and beach erosion along the central Adriatic coast of Italy: the case of Molise region - Carmen M. Rosskopf; Gianluigi Di Paola; David E. Atkinson; Germán Rodríguez; Ian J. Walker (Journal of Coastal Conservation, 2018)

Modelling the distribution of hard seabed using calibrated multibeam acoustic backscatter data in a tropical, macrotidal embayment: Darwin Harbour, Australia - P. Justy W. Siwabessy; Maggie Tran; Kim Picard; Brendan P. Brooke; Zhi Huang; Neil Smit; David K. Williams; William A. Nicholas; Scott L. Nichol; Ian Atkinson (Marine Geophysical Research, 2018)

Seasonal nutritional status in Norway lobsters, Nephrops norvegicus (L.): are females nutritionally compromised over the winter? - Andrew J. R. Watts; Amaya Albalat; Ian P. Smith; Robert J. A. Atkinson; Douglas M. Neil (Marine Biology Research, 2016)

HIV-associated distal neuropathic pain is associated with smaller total cerebral cortical gray matter - John R. Keltner; Christine Fennema-Notestine; Florin Vaida; Dongzhe Wang; Donald R. Franklin; Robert H. Dworkin; Chelsea Sanders; J. Allen McCutchan; Sarah L. Archibald; David J. Miller; George Kesidis; Clint Cushman; et al. (Journal of NeuroVirology, 2014)

Plant growth rates and seed size: a re‐evaluation - Lindsay A. Turnbull; Christopher D. Philipson; Drew W. Purves; Rebecca L. Atkinson; Jennifer Cunniff; Anne Goodenough; Yann Hautier; Jennie Houghton; Toby R. Marthews; Colin P. Osborne; Cloé Paul-Victor; Karen E. Rose; et al. (Ecology, 2012)
Small‐seeded plant species are often reported to have high relative growth rate or RGR. However, because RGR declines as plants grow larger, small‐seeded species could achieve higher RGR simply by virtue of their small size. In contrast, size‐standardized growth rate or SGR factors out these size effects. Differences in SGR can thus only be due to differences in morphology, allocation, or physiology. We used nonlinear regression to calculate SGR for comparison with RGR for 10 groups of species spanning a wide range of life forms. We found that RGR was negatively correlated with seed mass in nearly all groups, but the relationship between SGR and seed mass was highly variable. We conclude that small‐seeded species only sometimes possess additional adaptations for rapid growth over and above their general size advantage.

HIV-associated neurocognitive disorders before and during the era of combination antiretroviral therapy: differences in rates, nature, and predictors - Robert K. Heaton; Donald R. Franklin; Ronald J. Ellis; J. Allen McCutchan; Scott L. Letendre; Shannon LeBlanc; Stephanie H. Corkran; Nichole A. Duarte; David B. Clifford; Steven P. Woods; Ann C. Collier; Christina M. Marra; et al. (Journal of NeuroVirology, 2011)

Correlation of major depressive disorder symptoms with FKBP5 but not FKBP4 expression in human immunodeficiency virus–infected individuals - Erick T Tatro; Timothy B Nguyen; Chad A Bousman; Eliezer Masliah; Igor Grant; J Hampton Atkinson; Ian P Everall (Journal of NeuroVirology, 2010)

Turnover of quorum sensing signal molecules modulates cross‐kingdom signalling - Karen Tait; Holly Williamson; Steve Atkinson; Paul Williams; Miguel Cámara; Ian Joint (Environmental Microbiology, 2009)
Summary N ‐acylhomoserine lactone (AHL) quorum‐sensing molecules modulate the swimming behaviour of zoospores of the macroalga Ulva to facilitate the location of bacterial biofilms. Here we show that the intertidal surfaces colonized by Ulva are dominated by Alphaproteobacteria , particularly the Rhodobacteraceae family, and the Bacteroidetes family Flavobacteriaceae , and that this diverse assemblage both produces and degrades AHLs. N ‐acylhomoserine lactones could also be extracted from the surfaces of pebbles recovered from intertidal rock‐pools. Bacteria representative of this assemblage were isolated and tested for the production and degradation of AHLs, and for their ability to modulate zoospore settlement at different biofilm densities. Of particular interest was a Shewanella sp. This strain produced three major AHLs (OC4, OC10 and OC12) in the late exponential phase, but the longer‐chain AHLs were rapidly degraded in the stationary phase. Degradation occurred via both lactonase and amidase activity. A close relationship was found between AHL synthesis and Ulva zoospore settlement. The Shewanella isolate also interfered with AHL production by a Sulfitobacter isolate and its ability to enhance zoospore settlement in a polymicrobial biofilm. This influence on the attachment of Ulva zoospores suggests that AHL‐degrading strains can affect bacterial community behaviour by interfering with quorum sensing between neighbouring bacteria. More importantly, these interactions may exert wider ecological effects across different kingdoms.

Using temperature‐dependent changes in leaf scaling relationships to quantitatively account for thermal acclimation of respiration in a coupled global climate–vegetation model - OWEN K. ATKIN; LINDSEY J. ATKINSON; ROSIE A. FISHER; CATHERINE D. CAMPBELL; JOANA ZARAGOZA‐CASTELLS; JON W. PITCHFORD; F. IAN WOODWARD; VAUGHAN HURRY (Global Change Biology, 2008)
The response of plant respiration ( R ) to temperature is an important component of the biosphere's response to climate change. At present, most global models assume that R increases exponentially with temperature and does not thermally acclimate. Although we now know that acclimation does occur, quantitative incorporation of acclimation into models has been lacking. Using a dataset for 19 species grown at four temperatures (7, 14, 21, and 28 °C), we have assessed whether sustained differences in growth temperature systematically alter the slope and/or intercepts of the generalized log–log plots of leaf R vs. leaf mass per unit leaf area (LMA) and vs. leaf nitrogen (N) concentration. The extent to which variations in growth temperature account for the scatter observed in log–log R –LMA–N scaling relationships was also assessed. We show that thermal history accounts for up to 20% of the scatter in scaling relationships used to predict R , with the impact of thermal history on R –LMA–N generalized scaling relationships being highly predictable. This finding enabled us to quantitatively incorporate acclimation of R into a coupled global climate–vegetation model. We show that accounting for acclimation of R has negligible impact on predicted annual rates of global R , net primary productivity (NPP) or future atmospheric CO 2 concentrations. However, our analysis suggests that accounting for acclimation is important when considering carbon fluxes among thermally contrasting biomes (e.g. accounting for acclimation decreases predicted rates of R by up to 20% in high‐temperature biomes). We conclude that acclimation of R needs to be accounted for when predicting potential responses of terrestrial carbon exchange to climatic change at a regional level.

Occurrence and Distribution of Polycyclic Aromatic Hydrocarbons (PAHs) in Bolgoda and Beira Lakes, Sri Lanka - K. A. S. Pathiratne; O. C. P. De Silva; David Hehemann; Ian Atkinson; Robert Wei (Bulletin of Environmental Contamination and Toxicology, 2007)

Response of macroinvertebrates to warming, nutrient addition and predation in large-scale mesocosm tanks - Heidrun Feuchtmayr; Dermot McKee; Ian F. Harvey; David Atkinson; Brian Moss (Hydrobiologia, 2007)

Have the Harmful Effects of Introduced Rats on Islands been Exaggerated? - David R. Towns; Ian A. E. Atkinson; Charles H. Daugherty (Biological Invasions, 2006)

An improved multi-element measurement of mineral absorption in the piglet utilizing the fecal monitoring technique - Rosalind S. Gibson; Ian L. Gibson; Colin E. Webber; Stephanie A. Atkinson (Biological Trace Element Research, 1988)